Perbedaan Tingkat Stres Penderita Hipertensi Sebelum Dan Sesudah Pemberian Aromaterapi Lavender - Aliyah; Liyanovitasari; Suwanti (Journal of Holistics and Health Science, 2020)
Background: In 19 people out of every 1,000 residents of Central Java experience stress. In 2019, there were 87 adult hypertension sufferers at the Bergas Puskesmas. Stress in hypertensive patients can be reduced by giving lavender aromatherapy which stimulates the hypothalamus and relaxes the patient. The purpose of this study was to determine the significant effect of lavender aromatherapy on stress levels in hypertensive patients in Bergas Lor Village, Bergas District, Semarang Regency. Method: This was a quasi-experimental study with a pretest-posttest without control group design. The population in this study 87 people. The research sampling technique was purposive sampling with 18 respondents. The research instrument used the DASS42 questionnaire. Data analysis using dependent T-test. Results: The level of stress in hypertensive patients after being given lavender aromatherapy in the intervention group was 20.05 with 11 (61.1%). There was a significant difference in stress levels before and after giving lavender aromatherapy (p = 0.001). Suggestion: Lavender aromatherapy can be used to reduce stress levels due to hypertension so that the quality of life for people with hypertension is better. ABSTRAK Terdapat 19 orang dari setiap 1.000 warga Jawa Tengah mengalami stress. Tahun 2019 penderita hipertensi dewasa sejumlah 87 orang di Puskesmas Bergas. Stres pada pasien hipertensi dapat dikurangi dengan pemberian aromaterapi lavender yang merangsang hipotalamus dan merilekskan pasien. Tujuan penelitian ini adalah mengetahui pengaruh yang signifikan pemberian aromaterapi lavender terhadap tingkat stres pada penderita hipertensi di Desa Bergas Lor Kecamatan Bergas Kabupaten Semarang. Jenis penelitian quasi eksperimental dengan Pretest-Posttest without control Group Design. Populasi pada penelitian ini sebanyak 87 orang. Teknik sampling penelitian adalah purposive sampling dengan jumlah responden 18. Instrumen mpenelitian menggunakan kuesioner DASS42. Analisis data menggunakan uji dependent T-test. Tingkat stres pada penderita hipertensi sesudah diberikan aromaterapi lavender pada kelompok intervensi 20,05 dengan kategori ringan sebanyak 11 (61,1 %). Ada perbedaan tingkat stres yang signifikan sebelum dan sesudah pemberian aromaterapi lavender (p=0,001). Aromaterapi lavender dapat digunakan untuk menurunkan tingkat stres akibat menderita hipertensi sehingga kualitas hidup penderita hipertensi lebih baik.